Desain Teknologi Pembelajaran Dan Faktor-Faktor Yang Mempengaruhi Teknologi Pembelajaran - Mhd. Subhan; Ade Dermawansyah Purba; M. Virgian Raffy; Dwi Juliani; Hamid Maulana; Nurul Huda Maulidiyya; Aulia Fikri Ramadhan (Tamilis Synex: Multidimensional Collaboration, 2025)
This study aims to identify and analyze factors that influence the effectiveness of technology implementation in the learning process, both from internal and external aspects. The approach used in this study is the library research method, with data collection carried out through a review of various relevant literature on technology integration in education. The data is secondary and obtained from journals, scientific articles, and other written sources that support the author's analysis. The results of the study indicate that internal factors such as user competence (teachers and students), institutional policy support, curriculum readiness, and organizational infrastructure and culture have a significant influence on the success of implementing learning technology. Meanwhile, external factors such as government policies, socio-economic conditions, global technological developments, and the availability of digital infrastructure also determine the extent to which technology can be implemented optimally. In addition to its positive potential, the implementation of learning technology still faces various challenges, including limited internet access, low digital literacy, and problems with motivation and data security